The Intensifying Prefix prein a Corpus of Bulgarian and Ukrainian Parallel Texts - Derzhanski, Ivan; Siruk, Olena (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2019)
The subject of this study is the intensifying (elative) adjectival prefix prein Bulgarian and Ukrainian. The material comes from a bilingual corpus of parallel texts. The results demonstrate that the productivity of this prefix in the two languages is superficially similar, but its use shows significant mismatches, often motivated by structural and semantic peculiarities. The study also reveals some unexpected aspects of elative derivation in Ukrainian.